An assessment of the role of teachers in the academic performance of pupils in the national primary school examinations (NPSE) Yoni Mamaila Chiefdom, Tonkolili District - Samuel Karim; Exton Mohamed Zoker (Journal of Advanced Sciences and Mathematics Education, 2023)
The role of teachers in students' academic achievements in schools is key to the students' success and the evaluation of teachers in Sierra Leone. The objectives of this research are 1) Evaluate the contributions made by teachers towards students' performance in the NPSE at selected primary schools in Yoni Mamaila Chiefdom; 2) Identify the factors leading to the success or failure of students in the NPSE; 3) Uncover the obstacles limiting students' performance in schools. This study utilizes a mixed-method approach and a descriptive survey with a cross-sectional design. Data collection techniques included interviews, questionnaires, and documentation. The study was conducted in 4 selected schools with a research population of 200 individuals. The sampling technique used was purposive sampling, resulting in 60 respondents. The collected data were analyzed using descriptive data analysis. From the data analysis results, the conclusions drawn were 1) Teachers play an integral role in enhancing students' academic performance in the National Primary School Examination (NPSE); 2) Factors leading to the success or failure of students in the NPSE include the economic background of the family, the level of family education, and teachers' commitment to teaching; 3) There is a lack of support from stakeholders to assist students in obtaining necessary information. This study's findings indicate that learning based on dual representation significantly influences middle school students' academic achievements in single-variable linear equations.